The Epidemiological and Economic Impact of a Potential Foot-and-Mouth Disease Outbreak in Austria - Marschik, Tatiana; Kopacka, Ian; Stockreiter, Simon; Schmoll, Friedrich; Hiesel, Jörg; Höflechner-Pöltl, Andrea; Käsbohrer, Annemarie; Pinior, Beate (Frontiers in Veterinary Science, 2021)
An outbreak of foot-and mouth disease (FMD) in an FMD-free country such as Austria would likely have serious consequences for the national livestock sector and economy. The objective of this study was to analyse the epidemiological and economic impact of an FMD outbreak in Austria in order to i) evaluate the effectiveness of different control measures in two Austrian regions with different livestock structure and density, ii) analyse the associated costs of the control measures and the losses resulting from trade restrictions on livestock and livestock products and iii) assess the resources that would be required to control the FMD outbreak. The European Foot-and-Mouth Disease Spread Model (EuFMDiS) was used to simulate a potential FMD outbreak. Based on the epidemiological outputs of the model, the economic impact of the outbreak was assessed. The analysis of the simulations showed that the success of control strategies depends largely on the type of control measures, the geographical location, the availability of sufficient resources and the speed of intervention. The comparison of different control strategies suggested that from an economic point of view the implementation of control measures, such as pre-emptive depopulation of susceptible herds, would be efficient if the epidemic started in an area with high livestock density. Depending on the chosen control measures and the affected region, the majority of the total costs would be attributable to export losses (e.g. each day of an FMD epidemic costs Austria € 9-16 million). Our analysis indicated that the currently estimated resources for surveillance, cleaning and disinfection during an FMD outbreak in Austria would be insufficient, which would lead to an extended epidemic control duration. We have shown that the control of an FMD outbreak can be improved by implementing a contingency strategy adapted to the affected region and by placing particular focus on an optimal resource allocation and rapid detection of the disease in Austria. The model results can assist veterinary authorities in planning resources and implementing cost-effective control measures for future outbreaks of highly contagious viral diseases.